2015
DOI: 10.1038/ncomms8442
|View full text |Cite
|
Sign up to set email alerts
|

Fluctuations between multiple EF-G-induced chimeric tRNA states during translocation on the ribosome

Abstract: The coupled translocation of transfer RNA and messenger RNA through the ribosome entails large-scale structural rearrangements, including step-wise movements of the tRNAs. Recent structural work has visualized intermediates of translocation induced by elongation factor G (EF-G) with tRNAs trapped in chimeric states with respect to 30S and 50S ribosomal subunits. The functional role of the chimeric states is not known. Here we follow the formation of translocation intermediates by single-molecule fluorescence r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

22
136
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 65 publications
(161 citation statements)
references
References 67 publications
(204 reference statements)
22
136
3
Order By: Relevance
“…The positional change of the peptidyl-tRNA arising from the transition from State H to State H1 also causes the decrease of FRET between Cy3-labeled ribosomal protein L11 and Cy5-labeled peptidyl-tRNA (L11-t FRET) (see Fig. 1), which is consistent with the smFRET data of Adio et al [30]. The characteristic of 30S head rotations in Fig.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…The positional change of the peptidyl-tRNA arising from the transition from State H to State H1 also causes the decrease of FRET between Cy3-labeled ribosomal protein L11 and Cy5-labeled peptidyl-tRNA (L11-t FRET) (see Fig. 1), which is consistent with the smFRET data of Adio et al [30]. The characteristic of 30S head rotations in Fig.…”
Section: Discussionsupporting
confidence: 89%
“…In summary, our proposed pathway of ribosomal translocation is consistent with diverse single molecule and ensemble kinetic data presented in the literature [15, 21, 23, 27, 30, 31, 32, 33, 34, 35, 37]. With the pathway we study the dynamic relations among different transitions or events in the translocation pathway exhibited in the smFRET data and those exhibited in the ensemble kinetic data.…”
Section: Resultssupporting
confidence: 81%
See 1 more Smart Citation
“…Brackets are used to mark short-lived intermediates during normal translocation, similar to states captured by timeresolved cryo-EM along the translocation pathway (9). In the hybrid model, these intermediates have similar free energies in the absence of EF-G; they can spontaneously interconvert until their thermally driven fluctuations are blocked by conformational changes within EF-G that complete translocation (2). Both of these models include a power stroke early in translocation.…”
Section: Significancementioning
confidence: 99%
“…Translocation follows, and EF-G·GDP dissociates from the resulting POST-translocation complex (1). Recent studies (2)(3)(4) have clearly demonstrated that EF-G·GTP promotes translocation from either the classic or hybrid PRE complex, which contain tRNAs in the A/A and P/P or A/P and P/E sites, respectively (first letter 30S position, second letter 50S position).…”
mentioning
confidence: 99%